Montmorency tart cherry juice does not reduce markers of muscle soreness, function and inflammation following professional male rugby League match-play - Morehen, J. C.; Clarke, J.; Batsford, J.; Barrow, S.; Brown, A. D.; Stewart, C. E.; Morton, J. P.; Close, G. L. (European Journal of Sport Science, 2021)
Rugby League (RL) match-play causes muscle damage, inflammation and symptoms of fatigue. To facilitate recovery, nutritional interventions are often employed, including Montmorency cherry juice (MC). We assessed the effects of MC on recovery following RL match-play in eleven male professional RL players who played in two matches (7-days apart) with MC or placebo (PLB) supplemented for 5-days pre-match, matchday and 2-days post-match. Blood was collected 48h pre-match, half-time, within 30-mins of full-time and 48h post-match to assess Interleukin concentrations (IL-6, -8 -10). Self-reported sleep, fatigue, mood, stress, and muscle-soreness were assessed 24h pre and 24 and 48h post-matches with muscle function assessed 48h pre and 48h post-match. No differences in distance covered (6334 ± 1944 Vs 6596 ± 1776m) and total collisions (28 ± 11 Vs 29 ± 13) were observed between both matches. There was a small albeit significant increase in IL-6, -8 and -10 concentrations pre to post-match in both PLB (IL-6: 0.83 ± 0.92 Vs 2.91 ± 1.40, IL-8: 2.16 ± 1.22 Vs 3.91 ± 1.61 and IL-10: 2.51 ± 2.14 Vs 0.61 ± 0.50 pg.mL-1) and MC groups (IL-6: 0.53 ± 0.53 Vs 2.24 ± 1.73, IL-8: 1.85 ± 0.96 Vs 3.46 ± 1.12 and IL-10: 0.48 ± 0.50 Vs 2.54 ± 2.10 pg.mL-1), although there were no significant differences between groups (P<0.05). Likewise, there was a small but significant increase in muscle soreness (P=0.01) and reduction in CMJ (P=0.003) with no significant differences between groups. No significant changes in sleep, fatigue or mood (P>0.05) were observed pre to post-match or between groups. These data suggest MC does not affect the modest changes observed in cytokine responses and markers of recovery from RL match-play.